2017
DOI: 10.1007/s00246-017-1779-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing in Pediatric Cardiomyopathy

Abstract: Genetic testing is recommended in patients with dilated cardiomyopathy (DCM); however, limited studies demonstrate high yields of genetic testing in non-hypertrophic (HCM) patients. Furthermore, there is sparse genotype-phenotype data in pediatric DCM patients. We performed a retrospective review of 70 consecutive probands with cardiomyopathy (non-HCM) who underwent genetic evaluation. Mean age at presentation was 5.48 years. Echocardiography revealed mean ejection fraction of 32.4%. The LVEDd z score ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
10

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
1
11
2
10
Order By: Relevance
“…Previously, Belkaya et al found a significant proportion of children with myocarditis were carriers for rare genetic variants in cardiac-related genes, supporting this idea of genetic mutations increasing an individual's susceptibility to myocarditis. 7 It should be noted that Belkaya et al's yield (12%) and the 40-50% yield identified in other studies of non-ischemic cardiomyopathy 10,11 were lower than our yield of 62.5% for nonsyndromic forms. This discrepancy may be due to a variety of factors including sample size and study design.…”
Section: Discussioncontrasting
confidence: 74%
“…Previously, Belkaya et al found a significant proportion of children with myocarditis were carriers for rare genetic variants in cardiac-related genes, supporting this idea of genetic mutations increasing an individual's susceptibility to myocarditis. 7 It should be noted that Belkaya et al's yield (12%) and the 40-50% yield identified in other studies of non-ischemic cardiomyopathy 10,11 were lower than our yield of 62.5% for nonsyndromic forms. This discrepancy may be due to a variety of factors including sample size and study design.…”
Section: Discussioncontrasting
confidence: 74%
“…Of note, outcome was not specified for the 56 DCM patients. 38 In our study, which reports on the largest cohort of genetically tested children with DCM to date, we also observed decreased survival in children with a LP/P genetic variant. Our study is thus an important contribution to the mounting evidence that carrying a LP/P variant puts children at an increased risk of death or HTx.…”
Section: Yield Of Genetic Testing In Children With Dcmsupporting
confidence: 61%
“…19 Thus, understanding of the genetic causes of primary and idiopathic cardiomyopathy presenting in childhood is still extremely limited and based on studies typically with less than 150 participants. The lack of larger pediatric studies may explain why there is marked practice variation [20][21][22][23][24][25][26] despite guidelines that recommend genetic testing in children with cardiomyopathy. 12 The expected genetic heterogeneity and the number of private (or infrequent) variants in pediatric cardiomyopathy present an additional challenge to defining genetic architecture.…”
Section: Introductionmentioning
confidence: 99%